Correlation between blood pressure trajectory and hearing threshold among workers exposed to occupational noise in a city's rail transit enterprise - Zhan, Hongting; Wang, Qia; Chen, Xinmei; Liang, Zhiping; Li, Cong; Cao, Danyan; Yang, Aichu; Xiao, Minghui (Huan jing yu zhi ye yi xue = Journal of environmental & occupational medicine, 2025)
Background Hypertension is one of the chronic diseases with the highest prevalence in China, and a history of hypertension may potentially exacerbate hearing loss. Investigating the association between long-term blood pressure trends and hearing thresholds could contribute to hearing protection efforts for occupationally noise-exposed populations. Objective By investigating hearing thresholds and blood pressure levels among occupationally noise-exposed workers in an urban rail transit enterprise, and conducting a comprehensive analysis of the association between long-term blood pressure changes and hearing thresholds, to provide data references for health management strategies targeting occupationally noise-exposed workers. Methods Workers exposed to occupational noise at a rail transit enterprise were enrolled as study subjects and underwent pure-tone audiometry. Group-based trajectory modeling was employed to identify blood pressure trajectories. Categorical data were compared using chi-square tests, while normally distributed continuous variables were analyzed via t-tests and analysis of variance (ANOVA). Generalized linear mixed models (GLMMs) were subsequently applied toexamine associations between these trajectory groups and high-frequency hearing thresholds. Results Among 2 002 occupationally noise-exposed workers, the median (P25, P75) age was 32 (28, 35) years, with a median (P25, P75) working tenure of 7 (3, 10) years. In 2019, the positive hypertension rate was 9.04%, with a mean systolic blood pressure (SBP) of (122.97±11.60) mmHg and a mean diastolic blood pressure (DBP) of (76.37±9.02) mmHg. The hearing loss prevalence was 10.1%, showing bilateral high-frequency average hearing thresholds of (17.18±8.71) dB and speech-frequency average thresholds of (13.79±3.46) dB. Three distinct trajectory groups were identified for both SBP and DBP. Compared with other trajectory groups, the high-stable DBP group exhibited significantly higher hearing loss prevalence (χ2=6.34, P=0.042) and elevated high-frequency hearing thresholds (all Ps<0.05). Specifically, within the 30-39 age subgroup, the moderate-stable DBP group demonstrated 1.96 dB lower high-frequency thresholds than the high-stable group [β(95%CI): −1.96 (−3.61, −0.32), P=0.020]. Conclusion Among occupationally noise-exposed workers in a municipal rail transit enterprise, DBP trajectories demonstrated a positive association with high-frequency hearing thresholds. Notably, in young and middle-aged occupationally noise-exposed populations, DBP may exert a more critical influence than SBP on the progression of hearing loss.